Impact Of Knowledge Transfer On Malaysian Film Industry : A Case Study Of A Project In A Film Production House - Perumal, Vimala (2000)
In the Malaysian film industry, the competitive advantage and the awareness of the needs of knowledge has been arising to utilize the available technology and resources. To enhance our understanding of knowledge management, this project paper focuses on a specific purpose that is to create an understanding for how knowledge is transferred through a film project and how it can be utilized.